Synthesis of Nano Composite Particles by a Transferred Direct Current Thermal Plasma: Effects of Plasma Input Current - Kyu Park, Seung; Woo Park, Kyung; Chang Kim, Heon (Asian Journal of Chemistry, 2012)
Effects of input current on the characteristics of nano composite particles synthesized from a ZrVFe alloy ingot by transferred DC thermal plasma were investigated. The characteristics of the synthesized powder were analyzed by FE-SEM/EDX, XRD, PSA and BET. As the plasma input current increased from 120 to 160 A, the average particle size decreased from 83.2 to 47.8 nm, the particle size distribution became narrower and the surface area increased from 100.9 to 211.2 m2/g and the particle crystallinity was improved. In all cases, the generated composite particles were spherical.